2011
DOI: 10.1007/s00774-011-0330-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Paget’s bone disease in ethnic Thais: a series of four case reports and a review of the literature

Abstract: Paget's bone disease is quite common in some parts of Europe and countries inhabited by European emigrants, but it is rare in Asia. There have been only 13 reported cases in Southeast Asia, including one reported case from Thailand. Half of the previously reported cases had bone symptoms and the other half were asymptomatic, but were incidentally discovered when patients were being investigated for other medical problems. Here are reported cases of four asymptomatic patients who presented elevation of serum al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Some studies reported intranational regional differences (4-7) and mainly affects people over 55 years (3,8,9). However, the disease is extremely rare in Asia and Africa (1,2,(10)(11)(12)(13). For instance, the incidence rate in Japan is merely 0.00028% (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported intranational regional differences (4-7) and mainly affects people over 55 years (3,8,9). However, the disease is extremely rare in Asia and Africa (1,2,(10)(11)(12)(13). For instance, the incidence rate in Japan is merely 0.00028% (2).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to determine the genetic etiology of PDB and provide guidance for efficient molecular diagnosis. Considering the different genetic background between Chinese and Caucasian population (1,(10)(11)(12)14), the exploration of potential pathogenic genes of PDB in Chinese population also beneficial to explain the pathogenesis of PDB.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in patients over the age of 55 years and is more prevalent in men (M:F ratio: 2:1) 5,6 . PDB has an unusual geographic distribution, with an increased incidence in the United Kingdom, Germany, France, New Zealand, and Australia 6,7 , and being less common in China, Japan, India, Southeast Asia and America [8][9][10][11][12][13] . The incidence and severity of Paget's disease has decreased over the last 35 years [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, approximately 1-2% of the population are affected by PDB, with the northeastern region showing the highest prevalence [14]. The prevalence rate of PDB was reported to be low in Japan (0.00028%) [15] and is believed to be a rare disease in Asia [16,17].…”
Section: Introductionmentioning
confidence: 99%